Postoperative Digit and Hand Replantation Protocols: A Review of the Literature. Issue 15 (1st August 2021) - Chen, Christopher; Scott, Frank; Ipaktchi, Kyros R.; Lauder, Alexander
Abstract : Successful replantation and revascularization of the hand and digit require a skilled team with urgent access to an operating room with microsurgical capabilities. Although careful indications and surgical techniques contribute to success, postoperative management also plays a vital role in the survival of a replanted digit. Previous research has assessed surgical efficiency and techniques to conduct these procedures, but few studies evaluate postoperative protocols to care for patients undergoing these procedures. Because of the lack of high-level evidence specific to replantation, many common postoperative practices related to monitoring, anticoagulation, and diet have been inferred from elective microsurgical procedures, despite notable differences in operating conditions. The highest level of evidence pertaining to digital replantation was found with the use of peripheral nerve blockade, leeching/bleeding, and nicotine use. This review provides an in-depth evaluation of the literature and insight into the rationale and level of evidence that support each postoperative intervention. It highlights institutional variability and a paucity of high-level evidence pertaining to this topic while identifying the areas of future research.